ZnO-doped PFPAMA: a novel transparent conducting polymer for fast photodiodes - Ocaya, Richard O.; Erol, Ibrahim; Al-Sehemi, Abdullah G.; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Springer, 2022)
In this article, a new Schottky diode based on a transparent conducting polymer 2-(4-fluorophenyl)-2-oxoethyl-2-methylprop-2-enoate (PFPAMA) that is doped up to 5% with ZnO is presented. PFPAMA is a promising transparent polymer that is inclined towards n-type behavior with the potential to be used as an electron transport layer. Each device had the Al/p-Si:(PFPAMA:ZnO)/Al structure. The diode ideality factor was found to depend on bias and illumination but the calculated interface state density is lower by 3 orders of magnitude than for most reported Al/p-Si diodes, suggesting that the presence of the polymer suppresses interface states. The measured electrical and photoresponse characteristics confirm that the resulting diodes are suitable for fast photodiodes over the intensity range of dark to 100 mW/cm(2) whose performance can be optimized by ZnO doping. The application of functionalized polymers on p-silicon for sensing applications is an emerging field.
Keywords: Interface State Density; Schottky; Functionalization; Semiconductors; Fluorescence; Temperature; Extraction; Deposition; Silicon; Layers